Aplicativo móvil para mejorar la cobertura de monitoreo de medición de la temperatura ambiental del distrito de Punchana 2019 - Ferreyra Bernal, José Alberto (2021)
The purpose of this work is to develop a mobile application that allows us to improve the coverage of monitoring in the measurement of ambient temperature in the district of Punchana 2019, this research is of an application type with a descriptive level and with a non-experimental transactional design. The study sample will be made up of 10 researchers from the Peruvian Amazon Research Institute and for this purpose, non-probabilistic sampling of the convenience type will be used. The method of collecting information that was used was the collection of data in person at each point using thermometers through which it was possible to identify the variation in ambient temperature in different areas of the district, in this context it was possible to contrast and accept the research hypothesis: "The use of a mobile application will improve the coverage of monitoring in the measurement of ambient temperature in the district of Punchana 2019", as a result and based on the 50 geographical points for monitoring in the ambient temperature measurement using the application, the results were excellent, since there are more points sampled than those that SENAMI has, concluding that the monitoring coverage is EXCELLENT, that implies that "the use of a mobile application will allow to improve the coverage of monitoring in the measurement of ambient temperature in the district of Punchana”.